New Orientation of Arabic Syntax by Tammam Hassan and its Influence in Arabic Learning - Agung Prasetiyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Nahwu Arab by Tammam Hassan is not final. This means that syntaxis must be dynamic according to the needs of the times. Unfortunately, the syntaxis that had been coined on the early syntaxis experts only concerned with I'rab's problem or not on the matter of concrete meaning. So that dormitory and meaning become a separate thing. It is from this that Tammam Hassan has fought hard to make a new reading about syntaxis Arab and to dialogue with modern sciences. The result of his effort is born the theory of tadhafurul qaraain.The purpose of this research is first, want to explore the new orientation of the science of syntaxis according to Tammam Hassan. Secondly, to explore the influence of the new orientation of Nahwu science according to Tammam Hassan in Arabic learning.The results showed that 1) the new Arab syntaxis orientation initiated by Tammam Hassan covers aspects of ihyai, alsuni and ta'limi. In the ihyahi aspect, Tammam is committed to communicating Arab turots with the study of Western linguistic theories. Aspects of alsuni, Tammam divide the Kalim into seven parts of isim, fiil, properties, dharaf, shamor, khalofah, adat. He also shares qorinah into two parts: maknawi and lafdzi. While in aspect taklimi, consists of two things, namely theoretical and practical. 2) The new orientation of TA Hassan Arab syntaxis also has an impact on Arabic learning. Namely, effort to facilitate nahwu with his thoughts including dividing the jalim into seven parts; Three meanings: functional, lexical, and semantic; The division of the number: become ismiyah, fi'liyah and washfiyah; Speaking syntaxis as nidzam qorinah